Critical issues on violence against women : international perspectives and promising strategies (Global issues in crime and justice ;, 2019)
"Bringing together the very best in international scholarship with a rich variety of pedagogical features, this innovative new textbook on violence against women is specifically designed to provoke debate, interrogate assumptions and encourage critical thinking. This book presents a range of critical reflections on the strengths and limitations or responses to violent crimes against women and how they have evolved to date. Each section of the book introduces a specific response and offers an overview of contemporary practices and what is known about the effectiveness of these practices. Responding chapters in each section offer critical reflections on these responses and offer possible innovations in policy and practice. Themes covered include:The measurement of violence against women,Justice responses to intimate partner violence and sexual violence,Victims and advocacy,Behavior change programs for abusers,Prevention of violence against women.Each chapter is supplemented with learning objectives, critical thinking questions and lists of further reading to encourage discussion for students to appreciate the contested nature of policy. The innovative structure will bring debate alive in the classroom or seminar. The book is perfect reading for courses on violence against women, gender and crime, victimology and crime prevention"--